Barriers to Growth-Enhancing Structural Transformation : The Role of Subnational Differences in Intersectoral Productivity Gaps - Paul, Saumik (World Bank, Washington, DC, 2021)
The movement of workers from the farm sector to a more productive nonfarm sector has failed to generate significant gains in labor productivity in recent decades in many developing countries. This paper offers a new perspective on the barriers to growth-enhancing structural transformation, combining structural modeling with enterprise census data from Ghana. The paper argues that subnational differences in the intersectoral productivity gap between the nonfarm informal and formal sectors constrain the productivity gain from structural transformation. In Ghana, intersectoral productivity gaps among the richer regions are on average three times larger than among the poorer regions. The disparity in regional intersectoral productivity gaps is modeled as reflecting the disparity in the regional misallocation of labor between the informal and formal sectors. Misallocation is identified as the output wedge between the informal and formal sectors. Simulations suggest that a more productive nonfarm informal sector reduces the disparity in regional intersectoral productivity gaps and, in turn, increases national productivity and the contribution of structural transformation to national productivity. For example, a 90-percent reduction in the disparity in regional intersectoral productivity gaps raises Ghana’s national aggregate productivity by 11.9 percent and the contribution of structural transformation to productivity by 19.7 percent.